Design and fabrication of multifunction laptop cooler / Nadzirul Azizi Norizam and Zeno Michael - Norizam, Nadzirul Azizi; Michael, Zeno (School of Mechanical Engineering, 2023)
A laptop cooler or cooling pad is an accessory designed to reduce the operating temperature of laptop computers. This project aims to improve the design of laptop cooling pads to provide additional features beyond cooling. The primary objective is to determine the feasibility of adding multifunctional features to the cooling pad. The proposed design is focused on improving the user experience and enhancing the functionality of the device. The project will involve milling, cutting, and drilling to create the prototype device. The idea of multifunctionality is inspired by the innovation of multifunctional tables, which have become popular in recent years. The current design will focus on cooling the laptop, while also providing additional features that enhance the user's life. The project is motivated by the need to solve a common problem faced by laptop users, which is the inability of laptops to sufficiently cool themselves. By improving the design of laptop cooling pads, this project has the potential to offer a solution that improves the user's experience